2021
DOI: 10.1097/sla.0000000000004866
|View full text |Cite
|
Sign up to set email alerts
|

Blood Salvage and Autotransfusion With Single Leukoreduction Does Not Increase the Risk of Tumor Recurrence After Liver Transplantation for Advanced Hepatocellular Carcinoma

Abstract: The aim of this study was to determine whether autotransfusion of salvaged blood with single leukoreduction is associated with post-transplant tumor recurrence in patients with advanced hepatocellular carcinoma (HCC). Background: Previous studies have consistently demonstrated the safety of autotransfusion of salvaged and leukoreduced blood during liver transplantation for HCC. However, the effects of this technique remained unknown for advanced HCC. Methods: Of 349 patients who underwent living donor liver tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 42 publications
0
27
0
Order By: Relevance
“…We included two study pairs from the same institution (Kwon et al [20] and Han et al [21], Fujimoto et al [18] and Hirano et al [56]) despite a potentially overlapping patient population (overlap by 74 vs. 222, 46 vs. 50 IOCS-treated and analyzed subjects). Since enrollment periods and numbers of enrolled subjects varied, we assumed two different populations.…”
Section: Resultsmentioning
confidence: 99%
“…We included two study pairs from the same institution (Kwon et al [20] and Han et al [21], Fujimoto et al [18] and Hirano et al [56]) despite a potentially overlapping patient population (overlap by 74 vs. 222, 46 vs. 50 IOCS-treated and analyzed subjects). Since enrollment periods and numbers of enrolled subjects varied, we assumed two different populations.…”
Section: Resultsmentioning
confidence: 99%
“…Some investigators advocated the safety of this technique during LT in patients with hepatocellular carcinoma 6 based on findings showing an extremely low tumor recurrence rate. 93,94 Point-of-care coagulation monitoring devices have been widely used to avoid excessive allogeneic blood transfusion in LT. These viscoelastic tests (VETs) provide objective measures of global coagulation status at the bedside and allow clinicians to perform goal-directed coagulation management.…”
Section: Reduction Of Allogeneic Blood Transfusionmentioning
confidence: 99%
“…Moreover, the risk of HCC recurrence (both in intrahepatic and extrahepatic recurrence) or death showed a trend in favor of autotransfusion, although statistical significance was not reached. Because the amount of transfused allogeneic RBCs was controlled by matching, these results were not thought to be due to sparing of allogeneic RBCs and reduced immunomodulation with autotransfusion but due to the direct effects of autotransfusion (1).…”
Section: Charlotte Maulat Paul Boulard Fabrice Muscarimentioning
confidence: 99%
“…This issue remains a concern because the American Medical Council, in its report on autologous blood transfusion in 1986 promulgated a contraindication to the use of cell saver in cancer surgery based on a single case report in 1975, where a 52-year-old patient undergoing pneumonectomy was found to have malignant cells in salvaged blood (3,6). This dogma has become obsolete because since then, many authors have shown that the use of autologous blood in cancer patients can be safely used and does not impact the risk of neoplastic recurrence (1,3,7), event in HCC patients after LT (5,8). Moreover, in advanced HCC patients, who have greater metastatic potential, the uncertainty remains on the need of a single or a double-filtered leukoreduction during the treatment of the collected blood (9)(10)(11).…”
mentioning
confidence: 99%
See 1 more Smart Citation